2022
DOI: 10.1038/s41398-022-02227-y
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 regulates the arginase 1+ microglia phenotype through the initiation of TREM2 transcription, ameliorating depression-like behavior in mice

Abstract: The expression of the triggering receptor on myeloid cell-2 (TREM2) knockdown in microglia from the lateral habenula (LHb) reportedly induces depression-like behaviors in mice. However, the key molecular mechanism that mediates major depressive disorder (MDD) pathogenesis remains elusive. We herein show that Nrf2 regulates TREM2 transcription and effects TREM2 mRNA and protein expression. The activation of Nrf2 by sulforaphane (Nrf2 activator) increases the microglial arginase 1+ phenotype by initiating TREM2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…It has recently been shown that most, if not all, antidepressant drugs bring about their antidepressant effects by binding the tyrosine kinase receptor 2 (TrkB), a molecule tied to the action of BDNF [ 127 , 128 ]. The findings of the studies reviewed here quite match this concept; increased TrkB/BDNF signalling was related to antidepressant effects, and low levels were associated with depressive behaviour [ 11 , 50 , 66 , 69 , 84 , 93 , 103 , 111 , 120 ]. Increased activity also of protein kinase B (Akt-1), which is an antioxidant in the wingless-GSK pathway and carries on some of the biological [ 128 , 129 , 130 ] and clinical [ 131 ] actions of lithium, which also inhibits GSK-3β [ 132 , 133 , 134 ], was found to be associated with antidepressant effects in the studies included in this review [ 42 , 45 , 47 , 74 , 75 , 93 , 94 , 110 , 119 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…It has recently been shown that most, if not all, antidepressant drugs bring about their antidepressant effects by binding the tyrosine kinase receptor 2 (TrkB), a molecule tied to the action of BDNF [ 127 , 128 ]. The findings of the studies reviewed here quite match this concept; increased TrkB/BDNF signalling was related to antidepressant effects, and low levels were associated with depressive behaviour [ 11 , 50 , 66 , 69 , 84 , 93 , 103 , 111 , 120 ]. Increased activity also of protein kinase B (Akt-1), which is an antioxidant in the wingless-GSK pathway and carries on some of the biological [ 128 , 129 , 130 ] and clinical [ 131 ] actions of lithium, which also inhibits GSK-3β [ 132 , 133 , 134 ], was found to be associated with antidepressant effects in the studies included in this review [ 42 , 45 , 47 , 74 , 75 , 93 , 94 , 110 , 119 ].…”
Section: Discussionsupporting
confidence: 76%
“…The studies included here were based on different animal depression paradigms, with many studies using stress-induced DLB, mostly elicited by LPS [ 40 , 43 , 51 , 53 , 58 , 59 , 63 , 65 , 67 , 73 , 75 , 79 , 85 , 88 , 95 , 105 , 106 , 125 ], or through corticosterone or cortisol [ 44 , 46 , 80 , 87 , 98 ], while other studies used chronic unpredictable mild stress [ 61 , 72 , 76 , 83 , 93 , 96 , 97 , 99 , 100 , 101 , 106 , 108 , 111 , 122 , 124 ] or social defeat stress [ 50 , 52 , 88 , 102 , 107 , 120 ]. Two studies used tumour-related depression models [ 71 , 91 ], while just one study each used post-ovariectomised depression [ 121 ], pentylenetetrazol-induced seizures [ 116 ], maternal separation [ <...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SPT was used to assess anhedonia according to previously established protocols [8,30]. The mice were subjected to two bottles lled with either 1% sucrose or water following 24 h period of food and water deprivation.…”
Section: Sucrose Preference Test (Spt)mentioning
confidence: 99%
“…According to the reports of World Health Organization, depression affects about 3.8% of the population and causes huge economic burdens on individual, family and society. However, the pathogenesis of depression is yet unclear (He et al, 2022;Zhong et al, 2022), which results in two serious problems: i) only about 70% patients response to the first-line antidepressants; and ii) no objective laboratory methods are developed to diagnose depression Mojtabavi et al, 2022;Tian et al, 2023). Therefore, it is urgently needed to further explore the pathogenesis of depression.…”
Section: Introductionmentioning
confidence: 99%